Closure of the left atrial appendage using percutaneous transcatheter occlusion devices. (29th April 2020) - Gianni, Carola; Anannab, Alisara; Sahore Salwan, Anu; Della Rocca, Domenico G.; Natale, Andrea; Horton, Rodney P.
Abstract: Closure of the left atrial appendage (LAA) using percutaneous transcatheter occlusion devices is used for stroke prevention as an alternative for patients with a high risk and contraindications for long‐term oral anticoagulation use. In this manuscript, we will discuss the practical aspects of four among the available devices that provide percutaneous intravascular closure of the LAA: Watchman, Amulet, WaveCrest, and LAmbre.